Prevalence of Multidrug-Resistant Staphylococcus aureus among Medical Students in Comparison to Healthcare Workers in Benghazi City - Mohamad Alhammad,; Rashad Babiker,; Ziad Alibrahim,; Yaman Hamed, (AlQalam Journal of Medical and Applied Sciences, 2025)
Multidrug-resistant Staphylococcus aureus (MDR-SA), particularly methicillin-resistant strains (MRSA), represents a major public health challenge due to its ability to cause a variety of infections and withstand multiple antibiotics. This descriptive cross-sectional study aimed to figure out the prevalence and antibiotic resistance patterns of Staphylococcus aureus among medical students (community-acquired, CA) and healthcare workers (hospital-acquired, HA) in Benghazi, Libya. Between May and November 2020, a total of 146 nasal swabs were collected: 100 from hospital participants (25 physicians, 25 nurses, 25 workers, and 25 patients) and 46 from medical students. S. aureus was detected in 44% of hospital samples and 17% of community samples, with the highest colonization observed among nurses (39%), followed by doctors (27%), workers (18%), and patients (16%). All isolates were resistant to cefotaxime. Methicillin resistance was observed in 31.8% of HA isolates and 12.5% of CA isolates. Resistance to vancomycin, azithromycin, and meropenem was lower compared to methicillin. HA-MRSA isolates showed higher multidrug resistance, with significant associations between HA-MRSA and resistance to azithromycin and meropenem. In contrast, CA-MRSA isolates exhibited minimal resistance. These findings highlight a substantial burden of multidrug-resistant S. aureus, particularly in hospital settings, and emphasize the urgent need for robust infection control strategies and antibiotic stewardship programs to limit the spread of resistant strains in both healthcare and community environments in Benghazi.